Kejahatan Berbahasa dalam Media Sosial pada Pemilihan Bupati dan Wakil Bupati Pamekasan (Perspektif Ekologi Politik) - Ach. Adi Firmansyah; Yarno Yarno (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2024)
Hate speech, hoaxes, invitations/incitement, conspiracy, perjury, threats, bribery are forms of language crimes that are often found on social media. Political ecology studies the socio-political aspects of its environment. Meanwhile, the purpose of this study is to find language crimes found in TikTok social media which are studied based on the perspective of political ecology. The data source for this study is TikTok social media which was collected from October to November 2024. The main data collection techniques in this study are documentation techniques and note-taking techniques.Language crimes were found in the perspective of political ecology in the form of curses, slander and satire. The public environmental movement is a movement carried out by the general public with their attitudes, daily actions and words that express their reluctance or preference for certain ecosystems, certain lifestyles. Political parties are political means that bridge political elites to be able to participate in political contestation in a country that is characterized by finance, has its own political direction, carries group interests and contributes to political development as a political superstructure.